LOGISTIC OPPORTUNITIES AND CHALLENGES OF THE REPUBLIC OF ARMENIA IN INTEGRATING INTO INTERNATIONAL TRANSPORT CORRIDORS - Detloff, Maro (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
Integration into international transport corridors and global supply chains is one of the main prerequisites for expanding economic activity and increasing the competitiveness of national economies. In this context, the development of logistics systems is of key importance, contributing to the efficiency of freight transportation, increasing trade volumes and deepening regional cooperation. For the Republic of Armenia, which has a strategic location in the South Caucasus, the improvement of the logistics system is an important factor in terms of organizing international transportation and transit movement. However, currently, Armenia’s logistics capabilities are significantly limited due to geographical isolation, closed borders with Turkey and Azerbaijan, as well as shortcomings in infrastructure and customs processes. These problems are also reflected in the low positions of the country in the Logistics Performance Index (LPI), in particular, in the components of the efficiency of customs processes, infrastructure quality and timeliness of supply chains. The transport system of the Republic of Armenia is one of the strategic pillars of the country’s economic development and regional integration. As a key infrastructure of the national economy, it plays a significant role in the formation of the country’s logistics capabilities and the development of transit opportunities. Armenia’s logistics system is predominantly based on road transportation, which limits the opportunities for the development of multimodal transportation and hinders the country’s effective integration into regional transport corridors. The development of the "North-South" road corridor and the "Crossroads of Peace" strategic initiative can turn Armenia into a transit hub, connecting the ports of the Persian Gulf and the Black Sea. In parallel with the modernization of the logistics system of Armenia, it is important to simplify customs procedures, introduce digitalization and form effective management systems, which will contribute to reducing the costs and terms of cargo transportation. In a regionally competitive environment, where neighboring states have more developed infrastructure, a comprehensive strategic approach is needed so that Armenia can occupy the role of a regional transit hub and expand its economic ties in international transportation networks to increase competitiveness, as well as strengthen regional security and economic stability.